Ionic mechanisms of spinal neuronal cold hypersensitivity in ciguatera. (13th November 2015) - Patel, Ryan; Brice, Nicola L.; Lewis, Richard J.; Dickenson, Anthony H.
Abstract: Cold hypersensitivity is evident in a range of neuropathies and can evoke sensations of paradoxical burning cold pain. Ciguatoxin poisoning is known to induce a pain syndrome caused by consumption of contaminated tropical fish that can persist for months and include pruritus and cold allodynia; at present no suitable treatment is available. This study examined, for the first time, the neural substrates and molecular components of Pacific ciguatoxin‐2‐induced cold hypersensitivity. Electrophysiological recordings of dorsal horn lamina V/VI wide dynamic range neurones were made in non‐sentient rats. Subcutaneous injection of 10 nm ciguatoxin‐2 into the receptive field increased neuronal responses to innocuous and noxious cooling. In addition, neuronal responses to low‐threshold but not noxious punctate mechanical stimuli were also elevated. The resultant cold hypersensitivity was not reversed by 6‐(2‐[2‐fluoro‐6‐(trifluoromethyl)phenoxy]‐2‐methylpropylcarbamoyl)pyridine‐3‐carboxylic acid, an antagonist of transient receptor potential melastatin 8 (TRPM8). Both mechanical and cold hypersensitivity were completely prevented by co‐injection with the Nav 1.8 antagonist A803467, whereas the transient receptor potential ankyrin 1 (TRPA1) antagonist A967079 only prevented hypersensitivity to innocuous cooling and partially prevented hypersensitivity to noxious cooling. In naive rats, neither innocuous nor noxious cold‐evoked neuronal responses were inhibited by antagonists of Nav 1.8, TRPA1 or TRPM8 alone. Ciguatoxins may confer cold sensitivity to a subpopulation of cold‐insensitive Nav 1.8/TRPA1‐positive primary afferents, which could underlie the cold allodynia reported in ciguatera. These data expand the understanding of central spinal cold sensitivity under normal conditions and the role of these ion channels in this translational rat model of ciguatoxin‐induced hypersensitivity. Abstract : This study examines the neural mechanisms of sensory disturbances following ciguatoxin food poisoning. Subcutaneous Pacific ciguatoxin‐2 induces spinal neuronal hyperexcitability to cooling and mechanical stimuli dependent on peripheral Nav 1.8 and TRPA1, but not TRPM8 channels. Ciguatoxins may confer cold sensitivity to a subpopulation of cold‐insensitive Nav 1.8/TRPA1+ primary afferents, which could underlie cold allodynia reported in ciguatera.